The Effect of Green Bean Side Effect on Changes in Hemoglobin Levels in Pregnant Women with Anemia - Nara Lintan Mega Puspita; Fauzia Laili; Lindha Sri Kusumawati; Sa’adah; Yuli Astutik (Universitas STRADA Indonesia, 2021)
Hemoglobin is an iron-carrying oxygen transport protein protein in red cells in the blood of mammals and other animals. Hemoglobin consists of iron which is the carrier of O2. High and abnormal hemoglobin levels occur due to hemoconcentration due to dehydration. The number of red blood cells and hemoglobin molecules is not always increasing and decreasing simultaneously, for example the decrease in red blood cells along with slightly elevated or normal hemoglobin levels occur in cases of pernicious anemia, as well as slightly elevated or normal hemoglobin levels of hemoglobin decreases, occurs in iron deficiency anemia. The purpose of this research is to know the effect of green bean extract on changes of hemoglobin (Hb) level in Pregnant Women. The research design used was pre experimental research. The population in detail is all Pregnant Women, with acidental sampling technique in obtaining a sample of 16 people. The research instrument used is observation sheet and digital hemoglobin gauge and statistic test used is T test. The result of research of hemoglobin level before giving of green bean has average value (mean) is 10,494 and hemoglobin level after giving of green bean has average value (mean) is 11.238 this indicates an increase of hemoglobin level in student result of research done shows that there is an increase of Hb level in get p value 0,756 and 0,89. Then the T.Test data distribution test can be concluded p value <0.05 which means H0 rejected and H1 accepted